Electoral dynamics in Indonesia: money politics, patronage and clientelism at the grassroots. Edited by Edward Aspinall and Mada Sukmajati. Singapore: NUS Press, 2016, pp. 472. ISBN 978-981-4722-04-9 - Moten, Abdul Rashid (IIUM Press, International Islamic University Malaysia, 2017)
The editors of the book under review, Edward Aspinall, a professor of politics at the Australian National University, and Mada Sukmajati, a lecturer at Gadjah Mada University, Yogyakarta, rightly point out that scholars of elections and politics in the Third World do often assert the primacy of patronage and clientelism in elections, and that they hardly analyse the mechanisms through which vote-buying takes place (p. 8). The book under review tries to fi ll in this gap in the literature through an analysis of the 2014 legislative election campaign in several electoral districts in Indonesia. The overwhelming objective of this book is to identify “the chief mechanisms that Indonesian legislative candidates used to appeal to voters” (p. ix) to win elections in Indonesia. The introductory chapter provides a brief overview of relevant works on patronage and clientelism in Indonesian politics, explains the research design and goals, and summarizes the main fi ndings of the case studies.